Pemberdayaan siswa untuk mengendalikan masalah anemia - Waryana, Waryana; Santosa, Sabar; Oktasari, Rina (AcTion: Aceh Nutrition Journal, 2020)
Anemia was a health problem that was globally experienced by developed countries. Anemia was affected by many pregnant women, toddlers, and school-age children in Indonesia. The incidence of SEZs on women of fertile age was 49,44%. This study aimed to determine the effect of the implementation of anemia prevention in high school-based community empowerment on increasing the knowledge and participation of teachers, canteen managers, and school students. This was a quasi-experimental study. This design was a pre-post test with control. The population was high school students in the district of Srandakan Bantul Regency. Data were collected by interview, observation, and document search techniques. Data analysis was performed by means of different t-test.Â There was a difference in knowledge about controlling the problem of anemia at the end of treatment in the two groups (p= 0,000). There was a difference in students' participation in overcoming the problem of anemia at the end of the treatment in both groups (p= 0,000) The conclusion, the implementation of the prevention of anemia problems based on community empowerment on the knowledge and participation of students, teachers, and managers of the school canteen to controll anemia problem